Implementasi Model Pembelajaran Quiz Team Guru PAI Dalam Meningkatkan Keaktifan Belajar Peserta Didik - Abdul Manan; Rokim; Devi Septia Putri Beauty (Universitas Islam Lamongan, 2025)
This study is entitled Implementation of the Quiz Team Learning Model of Islamic Religious Education Teachers in Improving the Learning Activity of Class XI Students of SMA Negeri 1 Sukodadi Lamongan, the purpose of this study is to determine the implementation of the quiiz team learning model of Islamic Religiouis Eduication teachers in improving the learning activity of class XI stuidents of SMA Negeri 1 Suikodadi Lamongan, as well as to determine the suipporting and inhibiting factors for the implementation of the learning model. The research method uised is a quialitative research method. The resuilts of this stuidy indicate that the implementation of the quiiz team learning model of Islamic Religiouis Eduication teachers can improve the learning activity of stuidents, which can be seen from being active in discuissions, increasing participation, critical thinking skills, initiative in completing tasks, behavioral changes, and satisfactory learning ouitcomes. Suipporting factors for the implementation of the quiiz team learning model incluide saving costs and not buirdening both parties. The inhibiting factors incluide the lack of time allocation and the large nuimber of grouip members so that it is not optimal